Trade impacts of settled regional trade agreements in agriculture - Korinek, Jane (OECD [Paris]FR, 2009)
Analyzes in depth, three RTAs viz. ASEAN Free Trade Agreement (AFTA), the Common Market for Eastern and Southern Africa (COMESA) and the Southern Cone Common Market (MERCOSUR). Sheds light on whether and to what extent these agreements enhance trade in agricultural goods between their members, and direct trade from partners outside the RTA. Addresses the question of changes in the nature of trade due to, or concomitant with, implementation of the RTA.